Odpowiedzialność organizatora sieci franczyzowej wobec pracowników zatrudnionych przez uczestnika sieci - Bakalarz, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The franchise system is based on cooperation of unrelated entities. Each franchisee has an independent employer status and is responsible for employee’s damages. In this article, the author aims to analyze this basic principle. Franchisor has a contractual right to supervise realization of franchise’s package. However, in extremal cases, this control power may be abused. Franchisor may influence franchisee’s decision in the area of employment, limiting franchisee’s independence as an employer. The author analyzes this cases and an opportunity of recognizing franchisor as employer or joint employer of franchisee’s employees. The author, fi nally, examines whether the franchisor may be held liable for damages to the employees.
Keywords: franchise system; employer; liability; labour law